The Application Of The Law On The Crime Of Sexual Violence Against Minors In Relation To The Law On The Crime Of Sexual Violence (Study of Decision No.11 /Pid.Sus/2022/PN Wno) - Risma Florida; Papang Sapari; Suriyanto Suriyanto (Fakultas Hukum Dehasen, 2023)
The application of the law on sexual violence related to the law on sexual violence aims to create an environment without sexual violence in society. Legal certainty, justice and usefulness must be implemented, fulfilled and realized. Analysis of the application of law related to this law, the author will use a study of decision No.11 /Pid.Sus/2022/PN Wno, to determine the application of law - law no.12 of 2022 compared to the Supreme Court's decision on the case. The problem formulation of this thesis is: how the application of the law on sexual violence against minors is related to the law on sexual violence, the second problem formulation is how Law no.12 of 2022 protects victims of sexual violence from a human rights perspective. This type of research focuses on the study and application of rules or norms in positive law. The statutory approach is used to examine all laws and regulations related to the legal issues being studied. The conclusion of this research: 1. The application of the law against criminal acts of sexual violence against minors related to the law on criminal acts of sexual violence, is carried out by ensuring that victims obtain their rights from court decisions and these decisions can be implemented and benefits received by victims. 2. Protection of victims of sexual violence from a human rights perspective is realized by applying the principles of human rights contained in Law No.12 of 2022, namely assistance, protection, restitution rights, compensation, and execution which are the rights of victims, which fulfill the elements of victims' human rights. Restitution becomes the burden of the government if the perpetrator's assets cannot fulfill restitution.